Study on Factors to Improve Comfort of Stab-Resistant Vests Taking into Account Wearing Pressure and Movement Restriction (Journal of Fiber Bioengineering and Informatics, 2013)
In this paper, we investigated factors affecting movement restriction while wearing stab-resistant vestswith the aim of improving their comfort. We measured the contact area and pressure between the vestand a dummy, and performed sensory tests for movement restriction in the wearer's arms and upper bodyusing four vests of different sizes, weight and types of stab-proof material. The pressure distribution ofthe vests on a dummy was measured and cross-sections of dummy-worn vests were obtained by 3D scan.For these measurements, we controlled the tightness value, the ratio between vest waist circumferenceand dummy. In order to check the influence of vests on the movement of the arm and upper body,subjects evaluated movement restriction and the feeling of pressure on the waist, chest, abdomen andback. We discovered that vests tend to hang on the neck point, shoulder, chest and back. The pressureon the chest increased with increasing tightness value, while the abdomen was under pressured to aforward bending position. Thus, shorter stab-resistant materials at the vest front have less movementrestriction. In the arms, subjects reported less movement restriction when they felt that the shoulderarea was softer. Therefore, we discovered that contact area and pressure should be considered in thedesign of stab-resistant vests to improve the comfort of the wearer.